THE INFLUENCE OF TEACHER PERCEPTIONS OF THE NATIONAL ASSESSMENT AND UTILIZATION OF INSTRUCTIONAL MEDIA ON THE QUALITY OF HIGH SCHOOL LEARNING - Arfianto Wisnugroho; Haryanto Haryanto (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
Changes to the assessment system with the abolition of the UN (National Examination) and the implementation of the AN (National Assessment) elicited mixed reactions from teachers. AN is not a determinant of graduation but a school quality assessment program. It is necessary to study teachers' perceptions of AN and how these perceptions influence teachers' use of supportive learning media in improving the quality of learning. This study aims to determine the effect of teachers' perceptions of AN and instructional media on the quality of learning in senior high schools in South Aceh District. Quantitative research with a survey research design was carried out using a questionnaire sheet as a research instrument. Data analysis used inferential statistics, namely, linear regression and descriptive statistics, namely, the ideal assessment category. The results show that there is a significant influence between teachers' perceptions of AN and the use of instructional media on the quality of learning. Abstrak.Perubahan sistem asesmen dengan penghapusan UN (Ujian Nasional) dan penerapan AN (Asesmen Nasional) menimbulkan reaksi yang beragam dari kalangan guru. AN bukanlah penentu kelulusan namun program penilaian mutu sekolah. Kajian tentang persepsi guru terhadap AN dan bagaimana persepsi tersebut memengaruhi guru memanfaatkan media pembelajaran yang mendukung dalam peningkatan kualitas pembelajaran perlu dilakukan. Penelitian ini bertujuan untuk menganalisis pengaruh persepsi guru terhadap AN dan pemanfaatan media pembelajaran terhadap kualitas pembelajaran SMA di Kabupaten Aceh Selatan. Penelitian kuantitatif dengan desain penelitian survei dilakukan dengan menggunakan lembar angket sebagai instrumen penelitian. Analisis data menggunakan statistik inferensial yaitu regresi linear dan statistik deskriptif yaitu kategori penilaian ideal. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara persepsi guru terhadap AN dan pemanfaatan media pembelajaran terhadap kualitas pembelajaran.